Endoscopic bilateral deployment of multiple metallic stents for malignant hilar biliary strictures. (25th April 2013) - Kato, Hironari; Tsutsumi, Koichiro; Harada, Ryo; Okada, Hiroyuki; Yamamoto, Kazuhide
Abstract : Jaundice and cholangitis are associated with morbidity and mortality for patients with malignant hilar biliary strictures. Endoscopic biliary drainage is considered a useful procedure for palliation of unresectable malignant hilar biliary strictures. However, even today, the devices and methods to effectively achieve the drainage of these strictures are under debate. Endoscopic bilateral deployment of multiple metallic stents for malignant hilar biliary strictures is a feasible and useful procedure, providing long‐term patency and the preservation of functional liver volume. We report the cases of two patients who underwent endoscopic bilateral deployment of multiple metallic stents usingthe partial stent‐in‐stent method. Both of the patients had malignant hilar biliary stricture due to biliary tract cancer. The cancers were unresectable and the patients decided to receive chemotherapy. Before the chemotherapy, bilateral deployment of metallic stents was carried out and each patient has been receiving chemotherapy without occlusion of the metallic stents for several months.